Towards exact molecular dynamics simulations with machine-learned force fields - Stefan Chmiela (Nature Portfolio, 2018)
Simultaneous accurate and efficient prediction of molecular properties relies on combined quantum mechanics and machine learning approaches. Here the authors develop a flexible machine-learning force-field with high-level accuracy for molecular dynamics simulations.